2019
DOI: 10.1186/s12906-019-2510-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of berberine in animal models of Alzheimer’s disease: a systematic review of pre-clinical studies

Abstract: Background Berberine is an isoquinoline alkaloid extracted from various Berberis species which is widely used in East Asia for a wide range of symptoms. Recently, neuroprotective effects of berberine in Alzheimer’s disease (AD) animal models are being extensively reported. So far, no clinical trial has been carried out on the neuroprotective effects of berberine. However, a review of the experimental data is needed before choosing berberine as a candidate drug for clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 44 publications
1
51
0
1
Order By: Relevance
“…Growing evidence suggests that both AD and VaD are associated with diabetes [7,8,15,16,215,216], and the risk of dementia development could be reduced by successful intervention of diabetes and its comorbidities [13,215,217]. As summarized in previous review articles, berberine is a promising antidiabetic agent [20,21,24,163], and preclinical evidence suggests that berberine has neuroprotective effects [25,[218][219][220][221]. Here, we collectively evaluated the effectiveness of berberine as a treatment for diabetes-associated dementia by two database searches (Fig.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Growing evidence suggests that both AD and VaD are associated with diabetes [7,8,15,16,215,216], and the risk of dementia development could be reduced by successful intervention of diabetes and its comorbidities [13,215,217]. As summarized in previous review articles, berberine is a promising antidiabetic agent [20,21,24,163], and preclinical evidence suggests that berberine has neuroprotective effects [25,[218][219][220][221]. Here, we collectively evaluated the effectiveness of berberine as a treatment for diabetes-associated dementia by two database searches (Fig.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…In our next study, we plan to examine differences in gut microbiota in berberineand non-berberine treated mice as we hypothesize that these differences might be associated with differences in relapse propensity. Furthermore, a number of studies found that berberine has multifunctional properties and can inhibit the activity of important pathogenic enzymes, ameliorate intracellular oxidative stress, attenuate neuroinflammation, trigger autophagy, and protect neurons against recognition memory damage (de Oliveira et al, 2019;Yuan et al, 2019;Zhao et al, 2019). Undeniably, more research is needed to understand the effects of pre-extinction berberine intervention on relapse and uncover the underlying neurochemical and molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Berberine (33) has been shown to be neuroprotective through the Nrf2 upregulation and also alleviates rotenone-induced cytotoxicity by antioxidation and activation of PI3K/Akt signaling pathway in SH-SY5Y cells [82]. Neuroprotective effects of berberine have also been confirmed in animal models of Alzheimer's disease [83]. Berberine nanoparticles have shown protective effect against LPS-induced neurodegenerative changes [84].…”
Section: Berberine From Berberis Aristata DCmentioning
confidence: 99%